Histomorphometric analysis of the effects of grape seed extract (vitis vinifera) and low-level laser therapy (LLLT) on fracture healing (Annals of Medical Research, 2021)
Aim: In this study, we aim to investigate the effects of supplementary Grape Seed Extract (GSE) and Low-Level Laser Therapy (LLLT) on fracture healing, oxidant and anti-oxidant system in experimental mandible fractures.Material and Methods: 48 Wistar Albino rats (adult male, n=48) were used in our study. For all the subjects, a vertical fracture line through molar teeth in right mandibles was created and internally fixed using a four-hole microplate and four micro screws. Firstly, these subjects were randomly divided into 4 main groups (Control, GSE, LLLT, GSE+LLLLT) of 12 animals each, and then these were individually separated into two sub-groups of 7th and 21st days. The number of groups (n=6) was 8 in total. GSE of 300 mg/kg/day were provided to the subjects before they were sacrificed. LLLT of 23 J/cm2 was administered to two different points along with the fracture line at intervals of 48 hours for 7 days in the 7th day sub-groups and for 14 days in the 21st day sub-groups. After the procedure, while biochemical values such as TAS, TOS and OSI are measured; histopathologically it was examined in terms of capillary number and width, inflammatory cell, fibroblast count, collagen fibers, osteoblast count, ossification and mature bone formations.Results: For biochemical analyses, there was statistically significant difference only in TAS values on either the 7th or 21st day for the groups. Histological analyses showed that mandibular fracture healing were significantly better in the GSE and GSE+LLLT groups compared to the control group. The group of only LLLT had limited recovery while the combination of GSE+LLLT was the best for ossification.Conclusions: It is concluded that GSE may be one of the potential methods to accelerate fracture healings in mandibular fractures common in oral and maxillofacial surgery clinic and thus help patients recover in shorter time, and however LLLT can have positive effects on the process of ossification and recovery only when combined with the extract, which may result in better outcomes in clinical use.
Keywords: Low-level laser therapy; fracture healing; oxidative stress; free radicals; grape seed extract